2010
DOI: 10.1159/000316764
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stroke Patients Have Occult Malignancy More Often than Expected

Abstract: The aim of the present study was to investigate the frequency of having occult malignancy in patients with acute ischemic stroke and their clinical characteristics. We retrospectively enrolled 1,714 consecutive ischemic stroke patients within 7 days of onset. The patients were divided into two groups: the Non-M group had no malignancy, and the M group had malignancy. We compared the clinical characteristics of the two groups. Of 1,714 ischemic stroke patients, 51 patients (3.0%; M group) were newly diagnosed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 45 publications
(30 reference statements)
3
52
2
2
Order By: Relevance
“…Patients with cancer with cryptogenic stroke have been found to have higher D-dimer levels compared to patients with stroke without malignancy,7 a finding consistent with our patient. Although a number of cancers have been associated with a hypercoagulable state, adenocarcinomas have been significantly associated with cancer-related stroke 8.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with cancer with cryptogenic stroke have been found to have higher D-dimer levels compared to patients with stroke without malignancy,7 a finding consistent with our patient. Although a number of cancers have been associated with a hypercoagulable state, adenocarcinomas have been significantly associated with cancer-related stroke 8.…”
Section: Discussionsupporting
confidence: 92%
“…[4][5][6] In two studies, based on cancers detected within the first In three studies, prevalence was calculated on the basis of cancers detected solely during hospitalization and varied between 4.7 and 29.7 per 1000.…”
Section: Prevalence and Numbers Needed To Screen (Nns)mentioning
confidence: 99%
“…3 In the year before cancer is diagnosed when cancer is occult, the risk of stroke is almost twice that in the background population without occult cancer. [4][5][6][7][8] Comparative studies on prevalence of occult cancer in comparable background populations are missing. A prerequisite for implementation of cancer screening would be that prevalence of occult cancers in the stroke population is markedly higher than in the background population.…”
Section: Introductionmentioning
confidence: 99%
“…Uemura et al reported that hemoglobin levels were reduced in cancer patients compared with patients with no malignancy. 12 Their explanation for the reduced hemoglobin levels in cancer patients was the general condition of these patients as a result of cancer cachexia or gastrointestinal bleeding in gastrointestinal cancer patients. The present results support those of Uemura et al; hemoglobin levels in the cancer groups were lower than the non-cancer group in the present study.…”
Section: Figurementioning
confidence: 99%